2012
DOI: 10.1603/an11100
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification ofCeratitis capitata(Diptera: Tephritidae) using DNA Sequences of the COI Barcode Region

Abstract: The utility of the cytochrome oxidase I gene barcode region for diagnosis of the Mediterranean fruit fly, Ceratitis capitata (Weidemann), is evaluated using African fruit fly collections. The method fails to discern C. capitata from its close relative Ceratitis caetrata Munro, based on genetic distances, parsimony networks, or nucleotide diagnostic characters observed in the DNA barcode sequences. When treated as a single taxon, it is possible to discern the C. capitata + C. caetrata lineage from other Ceratit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 59 publications
1
69
0
Order By: Relevance
“…Barr et al (2012) investigated the utility of DNA barcoding for molecular identification of several tephritid pests, including Ceratitis cosyra . They suggested that the mango fruit fly might include cryptic species.…”
Section: Introductionmentioning
confidence: 99%
“…Barr et al (2012) investigated the utility of DNA barcoding for molecular identification of several tephritid pests, including Ceratitis cosyra . They suggested that the mango fruit fly might include cryptic species.…”
Section: Introductionmentioning
confidence: 99%
“…Detection can be accomplished through monitoring of commercial Þelds and surrounding areas for an insect, especially when it can be visually identiÞed (Beers et al 1993). However, when visual identiÞcation is not possible, then genetic methods can be useful for distinguishing benign from harmful taxa (Rugman-Jones et al 2009, Virgilio et al 2009, Barr et al 2012, Liu et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…three county area, saving the WSDA, USDA, and the local county pest control board approximately US$0.5 million in monitoring, inspection, and control costs. Using genetic methods to detect harmful pest species is not a new approach (Rugman-Jones et al 2009, Virgilio et al 2009, Liu et al 2011, Barr et al 2012). However, our study underscores how integrating genetic methods into a formal Þeld survey can be extremely useful, if not critical, for effective insect management, because rapid identiÞcation can avert costly quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (149 out of 165) of ßies collected in California had DNA extracted using the KingFisher method. An additional 16 samples had DNA extracted from a leg using the DNeasy Blood and Tissue Kit (Qiagen, Valencia, CA) following the description of Barr et al (2012).…”
Section: Materials Andmentioning
confidence: 99%
“…Sequencing was performed using three BigDye-labeled dideoxynucleotide triphosphates (v3.1 dye terminators, Applied Biosystems, Foster City, CA) and run on an ABI 3730XL DNA analyzer at the Huck InstituteÕs Nucleic Acid Facility (Pennsylvania State University). All sequences were edited and assembled into contigs using the program Sequencher v5 (Genecodes, Ann Arbor, MI), aligned using MEGA5.1 (Tamura et al 2011), and evaluated for pseudogenes as described by Barr et al (2012).…”
Section: Materials Andmentioning
confidence: 99%